2016
DOI: 10.18786/2072-0505-2016-44-2-227-233
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Diagnostics of Tumors With Upconversion Nanoparticles

Abstract: Актуальность. Для повышения качества онко-логических операций необходимо полностью удалить опухоль, включая метастазы, свести к минимуму повреждения здоровых тканей и со-кратить время операции. Современные методы детектирования, в основе которых лежит рент-геновская компьютерная томография, а также магнитно-резонансная томография, определяют опухоль, когда ее объем становится достаточ-но большим (содержит более 10 миллиардов клеток). В этой связи актуальной задачей пред-ставляется повышение чувствительности и … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…The signal from the nanoparticles modified by ionizable lipid 3 was observed up to 1.5 h, whereas nanoparticles modified with cysteine-containing PEG-lipid 4 were visible for more than 3 h, more than 15-fold longer than the result obtained for the commercially available PEG-lipid 1. In addition, the circulation time of nanoparticles coated with PEG-lipid 4 was more than 3-fold longer than the time of other upconverting nanoparticles with different shells described in the literature [23,24]. Analysis of the microphotographs using ImageJ (NIH, Bethesda, MD, USA) software showed that the nanoparticle number was reduced from 260 to 18 over 10 min (Figure 2D), whereas only a moderate decrease in fluorescence intensity was observed (Figure 2E).…”
Section: Figure 2 Synthesis Of Upconverting Nanoparticles (A)mentioning
confidence: 80%
“…The signal from the nanoparticles modified by ionizable lipid 3 was observed up to 1.5 h, whereas nanoparticles modified with cysteine-containing PEG-lipid 4 were visible for more than 3 h, more than 15-fold longer than the result obtained for the commercially available PEG-lipid 1. In addition, the circulation time of nanoparticles coated with PEG-lipid 4 was more than 3-fold longer than the time of other upconverting nanoparticles with different shells described in the literature [23,24]. Analysis of the microphotographs using ImageJ (NIH, Bethesda, MD, USA) software showed that the nanoparticle number was reduced from 260 to 18 over 10 min (Figure 2D), whereas only a moderate decrease in fluorescence intensity was observed (Figure 2E).…”
Section: Figure 2 Synthesis Of Upconverting Nanoparticles (A)mentioning
confidence: 80%
“…Кроме того, необходимо отметить люминесцентные свойства ФМН и НАФ, которые позволяют использовать комбинацию этих препаратов не только для терапии опухоли, но и для визуализации опухолевого очага (так называемая тераностика). Перспективы применения НАФ в качестве контрастного агента для маркирования опухоли обсуждались нами ранее [20].…”
Section: Discussionunclassified